Intercultural Communicative Competence: A Pedagogical Critic in English Language Teaching - Daud, Enni Akhmad; Basalama, Nonny; Hidayati Otoluwa, Moon; Taufiqrianto Dako, Rahman (Al-Lisan: Jurnal Bahasa, 2024)
Research about Intercultural Communicative competence with its relation to English language has been discussed among scholars. However, the discussion about how to integrate it into teaching and learning English in the classroom remains lacking exploration. This research investigated the lecturers’ ways of integrating ICC components in teaching and learning English. This research involved four lecturers of the English Education Department IAIN Sultan Amai Gorontalo which was taken purposively. The participants were the lecturers who taught receptive and productive skills.   It employed a descriptive qualitative method.  Data were collected through interviews and observation sheets and analyzed using thematic analysis. It found three lecturers’ ways of integrating ICC in teaching English, first, the teachers guided students to have intercultural knowledge, intercultural attitude, and intercultural skills in teaching the English language. Second, the teachers contrasted between English language culture and Indonesian culture. Third, the teachers asked the students to practice the activities which addressed to intercultural knowledge, intercultural attitude, and intercultural skills. This research implied that ICC is competence should be mastered by the English learners in the digital era.